Analisis Akuntabilitas Dan Efektivitas Pengelolaan Dana Desa Dalam Meningkatkan Pembangunan Desa - Rima Nurmala; Ade Sudarma; Evi Martaseli (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This study aims to explain the current condition of the development of Cisiitu Village, the management of Village Funds, the driving and inhibiting factors for Village Fund management, the effectiveness and accountability of Village Fund management in enhancing village development. The method used in this study uses a descriptive qualitative method. Data collection methods in this study are observation, interviews and documentation. The type of data used is primary data. The results of his research show that (1) development conditions in Cisitu Village are maximized, (2) Village Fund Management in Cisitu Village is used in accordance with planned objectives and in accordance with agency theory, (3) The most influential supporting factor is active community participation . While the inhibiting factor is the lack of careful and strategic planning, (4) The effectiveness of Village Fund management in Cisitu Village is already in the very effective category, because in 2019 - 2022 the realization reached the target of more than 100%, (5) Village Fund management accountability in the Village Cisitu has reached the very economical category, because in 2019 - 2022 the realization of spending has reached 100% of the spending budget.